Pengaruh Model Pembelajaran POE (Predict-Observe-Explain) terhadap Keterampilan Proses Sains Siswa Kelas XI pada Materi Larutan Penyangga - Faizah Aulia; Maria Paristiowati; Elsa Vera Nanda (LPPM Universitas Negeri Jakarta, 2025)
The implementation of chemistry learning in schools is not yet optimal because it tends to only prioritize products, namely students' cognitive learning outcomes, while students' science process skills are put aside. Therefore, this research aims to determine the effect of the POE (Predict-Observe-Explain) learning model on class XI students' science process skills in buffer solution material. The participants in this research were 86 class XI students at SMA Negeri 1 South Tangerang in the even semester of the 2023/2024 academic year. The research method used was quasi-experimental with a Pretest Posttest Nonequivalent Control Group Design research design. This research sample was taken using a purposive sampling technique so that class XI MIPA 4 was obtained as a control class which applied the 5M learning model and class Quantitative data were analyzed using SPSS 29 with the Mann Whitney U test and Wilcoxon test. The results show that the science process skills of experimental class students are greater than those of control class students. Therefore, it can be concluded that the application of the POE (Predict-Observe-Explain) learning model has a positive effect on class XI students' science process skills in buffer solution material.